Computerized acoustic assessment of treatment efficacy of nebulized epinephrine and albuterol in RSV bronchiolitis - Talmon Gil; Tov Naveh; Shoval Shay; Elias Nael; Beck Raphael; Godfrey Simon; Bentur Lea (BMC, 2007)
Abstract Aim We evaluated the use of computerized quantification of wheezing and crackles compared to a clinical score in assessing the effect of inhaled albuterol or inhaled epinephrine in infants with RSV bronchiolitis. Methods Computerized lung sounds analysis with quantification of wheezing and crackles and a clinical score were used during a double blind, randomized, controlled nebulized treatment pilot study. Infants were randomized to receive a single dose of 1 mgr nebulized l-epinephrine or 2.5 mgr nebulized albuterol. Computerized quantification of wheezing and crackles (PulmoTrack®) and a clinical score were performed prior to, 10 minutes post and 30 minutes post treatment. Results were analyzed with Student's t-test for independent samples, Mann-Whitney U test and Wilcoxon test. Results 15 children received albuterol, 12 received epinephrine. The groups were identical at baseline. Satisfactory lung sounds recording and analysis was achieved in all subjects. There was no significant change in objective quantification of wheezes and crackles or in the total clinical scores either within the groups or between the groups. There was also no difference in oxygen saturation and respiratory distress. Conclusion Computerized lung sound analysis is feasible in young infants with RSV bronchiolitis and provides a non-invasive, quantitative measure of wheezing and crackles in these infants. Trial registration number: ClinicalTrials.gov NCT00361452